Development of a new design approach for weldings. (13th September 2017) - Stroetmann, Richard; Kästner, Thoralf; Werner, Lars
ABSTRACT: The application of high strength steels provides economic and ecological advantages in many types of constructions, due to the resource‐conserving material use. However, for welded constructions, some of these advantages are partially offset by conservative design rules and more complicated execution regulations. The objective of the ongoing AiF‐FOSTA research project P1020 is the development of principles, which lead to significant improvements of design and execution rules for welded connections of high strength steel structures. The development of design rules aims at a simpler and economically more efficient execution. This paper gives an overview of the research project P1020, including the design model, the assessment of the welding processes and the parametric studies, consisting of load bearing tests and numerical simulations. It describes the development of the flat tensile test method for the assessment of the welding behaviour and the structural analysis of welded joints for parametric studies.